1995
DOI: 10.1111/j.1751-0813.1995.tb15036.x
|View full text |Cite
|
Sign up to set email alerts
|

The minor role of pigs in outbreaks of foot‐and‐mouth disease of northern Thailand

Abstract: A study was undertaken in northern Thailand to examine the involvement of pigs in outbreaks of foot-and-mouth disease (FMD). Data were collected by surveying selected villages, by serological monitoring of pigs and by investigating outbreaks. Fifty-three of 58 villages (91%) surveyed reported that pigs did not develop FMD during the most recent outbreak. The source of 49/60 (82%) outbreaks was attributed to either recent purchases of infected cattle and buffalo or commingling of cattle and buffalo with stock f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…With most farmers using the communal grazing method, the movement of large ruminants to communal grazing areas enables contact with animals from other locations, increasing the risk of contracting diseases, particularly FMD, as previously reported by other studies (Chamnanpood et al, 1995;Cleland et al, 1995), and recently reviewed by Blacksell et al (2019). During FMD outbreaks, confining and feeding cattle on cut grasses reduces the likelihood of infection, with this practice proposed to reduce the risk of spread of FMD virus by reducing the direct contact between healthy and infected animals (Cleland et al, 1996).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…With most farmers using the communal grazing method, the movement of large ruminants to communal grazing areas enables contact with animals from other locations, increasing the risk of contracting diseases, particularly FMD, as previously reported by other studies (Chamnanpood et al, 1995;Cleland et al, 1995), and recently reviewed by Blacksell et al (2019). During FMD outbreaks, confining and feeding cattle on cut grasses reduces the likelihood of infection, with this practice proposed to reduce the risk of spread of FMD virus by reducing the direct contact between healthy and infected animals (Cleland et al, 1996).…”
Section: Discussionmentioning
confidence: 53%
“…With most farmers using the communal grazing method, the movement of large ruminants to communal grazing areas enables contact with animals from other locations, increasing the risk of contracting diseases, particularly FMD, as previously reported by other studies (Chamnanpood et al., 1995; Cleland et al., 1995), and recently reviewed by Blacksell et al. (2019).…”
Section: Discussionmentioning
confidence: 59%
“…The World Reference Laboratory (WRL) for FMD in Pirbright in the United Kingdom (UK) provides information on the genetic relationships between field isolates submitted from member countries. There are a limited number of scientific publications on FMD epidemiology in South-East Asia, with most of the work arising from studies conducted in Thailand (2,3,4,5).…”
Section: Overview Of the Status Of Foot And Mouth Disease In South-eamentioning
confidence: 99%
“…Interestingly, studies in Vietnam have demonstrated that persistently infected animals do not transmit the disease animals to naive animals [31]. In SEA, pigs have been reported as both refractory [32] and highly susceptible [5] to FMD infection, illustrating the important role of adaption and species susceptibility to different FMD strains such as the pig-adapted O/CHY topotype [33]. The role of small ruminants in the epidemiology of FMD in SEA is unclear which highlights the need for further studies to understand the function of all species for disease control or eradication.…”
Section: Risk Factors That Influence the Spread Of Fmd In Seamentioning
confidence: 99%